Are Coups Really Contagious? An Extreme Bounds Analysis of Political Diffusion. (February 2018) - Miller, Michael K.; Joseph, Michael; Ohl, Dorothy
Protests and democratic transitions tend to spread cross-nationally. Is this true of all political events? We argue that the mechanisms underlying the diffusion of mass-participation events are unlikely to support the spread of elite-led violence, particularly coups. Further, past findings of coup contagion employed empirical techniques unable to distinguish clustering, common shocks, and actual diffusion. To investigate which events diffuse and where, we combine modern spatial dependence models with extreme bounds analysis (EBA). EBA allows for numerous modeling alternatives, including diffusion timing and the controls, and calculates the distribution of estimates across all combinations of these choices. We also examine various diffusion pathways, such as contagion among trade partners. Results from nearly 1.2 million models clearly undercut coup contagion. In comparison, we confirm that more mass-driven political events robustly spread cross-nationally. Our findings contribute to studies of political conflict and contagion, while introducing EBA as an effective tool for diffusion scholars.